Evaluation of early electrocardiographic changes after successful percutaneous stent implantation to isolated coarctation of aorta - (:unkn) unknown (CHURCHILL LIVINGSTONE INC MEDICAL PUBLISHERS, 2020)
Background: Coarctation of aorta (CoA) is a congenital obstructive lesion characterized by narrowing of the aorta in which concludes as increase in afterload. Percutaneous stent implantation to CoA is a treatment of choice in older children and adults. Pathology related to CoA mainly caused by increased afterload and left ventricular hypertrophy. Electrocardiographic (ECG) findings are also related to left ventricular hypertrophy (LVH). Evidence shows that, in variety of diseases, the correction of the pathology might normalize ECG findings and ventricular dysfunction related to increase in afterload. Therefore the aim of this study was to compare the preand postprocedural ECG findings of the patients who underwent percutaneous intervention for isolated CoA. Methods: After exclusion criterion was applied, 30 patients were included into study, retrospectively. ECG records before the procedure and 3 months after the procedure of the patients were evaluated. The parameters related to LVH, ventricular and atrial conduction were evaluated and compared between preand post procedural ECG records. Results: The findings showed that parameters of atrial conduction including P wave maximum duration (p < 0.001) and p wave dispersion (p < 0.001) were significantly decreased after stent implantation. Additionally, ventricular repolarization parameters including QT duration (p = 0.039), Tpe interval (p < 0.001), Tpe / QT (p = 0.038) and Tpe / QTc (p = 0.003) were significantly decreased after stent implantation. Sokolow-Lyon criteria (p < 0.003) and voltage in selected leads were significantly decreased after intervention. Conclusion: Percutaneous intervention to CoA might regress LVH parameters in ECG and improve atrial and ventricular repolarization in ECG, which might lead to decreased event of atrial and ventricular arrhythmias in patients with isolated CoA. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: LEFT-VENTRICULAR MASS; HEART RHYTHM SOCIETY; INTERNATIONAL-SOCIETY; MYOCARDIAL STRETCH; AMERICAN-COLLEGE; QT INTERVAL; TRANSCATHETER; STENOSIS; HYPERTROPHY; ARRHYTHMIAS